2017
DOI: 10.1371/journal.pone.0181555
|View full text |Cite
|
Sign up to set email alerts
|

Breast tissue ablation with irreversible electroporation in rabbits: A safety and feasibility study

Abstract: Background and aimIrreversible electroporation (IRE) was confirmed to control several solid tumors effectively in vivo. Our preclinical study aimed to assess the feasibility and safety of IRE in the breast of rabbit.MethodsThirty New Zealand white rabbits were randomly divided into 3 groups of 10 rabbits (control group, IRE group A, and B). Two mono-electrode needles were inserted into the breast tissue by percutaneous puncture. Electrocardiogram and vital signs were monitored before, during, and after ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…After the IRE ablation, the pigs were closely monitored by experienced veterinarians every 8 hr for 24 hr, and no critical complications were observed. Subsequent necropsy showed no evidence of perforation, peritonitis, or injury of vascular structures, similar to other studies conducted in different organs [ 21 - 23 ]. Apoptosis, the result of electroporation, was confirmed by histopathologic evaluation; however, the evaluation showed insufficient depth of the ablated ductal wall.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…After the IRE ablation, the pigs were closely monitored by experienced veterinarians every 8 hr for 24 hr, and no critical complications were observed. Subsequent necropsy showed no evidence of perforation, peritonitis, or injury of vascular structures, similar to other studies conducted in different organs [ 21 - 23 ]. Apoptosis, the result of electroporation, was confirmed by histopathologic evaluation; however, the evaluation showed insufficient depth of the ablated ductal wall.…”
Section: Discussionsupporting
confidence: 85%
“…Subsequent necropsy showed no evidence of perforation, peritonitis, or injury of vascular structures, similar to other studies conducted in different organs. [21][22][23] Apoptosis, the result of electroporation, was confirmed by histopathologic evaluation; however, the evaluation showed insufficient depth of the ablated ductal wall. Compared with other studies, our study used lower energy levels as the wall of the bile duct with a tunnel-type structure is thinner than that of other solid organs such as the liver and pancreas.…”
Section: Discussionmentioning
confidence: 89%
“…Transmission electron microscopy (TEM) studies of electroporated tissue are very scarce, and virtually non-existent scanning electron microscope (SEM) studies 9 . To our knowledge, there are two studies that describe TEM findings in uterine cervix and breast in rabbits 10,11 and a study in pig liver which uses TEM methodology after IRE using needle but not parallel-plate electrodes 12 .…”
Section: Introductionmentioning
confidence: 99%
“… 31 On the other hand, in vivo studies have been reported in animal models comprising nude mice 32 and rabbits. 33 The results reported in these works suggest that IRE may be a promising approach for patients with breast cancer who are not eligible for surgical excision. In addition, numerical modeling of electric field distribution represents a useful tool to validate the required voltage to fully expose the target to the electric field determined from in vitro experiments.…”
Section: Introductionmentioning
confidence: 91%
“…Nonetheless, more experimental evidence regarding the treatment of breast cancer with IRE is required, since reports on this field remain limited. 31 - 34 …”
Section: Introductionmentioning
confidence: 99%